An algorithm directed computer aided software engineering (CASE) environment for C. - Ouerd, Messaouda. (University of Ottawa (Canada), 1990)
The objectives of computer aided software engineering (CASE) systems are to improve productivity during the software development process and the quality of software using software engineering concepts via automation of the software development life cycle. This will result in a reusable software and will decrease the cost and time of software development and maintenance. The main concern in this thesis is with describing the features of a particular software understanding environment for C. An algorithm directed computer aided software engineering environment for C language has been developed and implemented. The system has been implemented on a Sun Workstation using the Sunview window interface. It provides computer aided software engineering tools which: (1) Assist the user in developing structured algorithms for procedural languages; (2) Automatically transform a structured algorithm into a corresponding program; (3) Redocument the resulting C program (or any C program developed using any other technique) in an organized representation.
Keywords: Computer Science.